In vitro and in vivo antioxidant and antidiabetic activity studies on standardized extracts of two Bidens species. Issue 6 (4th September 2017) - Icoz, Ulku G.; Orhan, Nilufer; Altun, Levent; Aslan, Mustafa
Abstract: Aim of this study is to evaluate the in vivo and in vitro antidiabetic and antioxidant profile of standardized ethanol extracts of Bidens cernua L. var. radiata and B. frondosa L. Acute hypoglycemic activity of extracts were investigated on normoglycemic, glucose loaded and streptozotocin‐induced diabetic rats. Sub‐acute antidiabetic effect was investigated during the 8 days experiment. Both the extracts exhibited promising and significant hypoglycaemic effect in all tested in vivo models. Acute antidiabetic effect of B. cernua and B. frondosa were found as 40% and 42% at 500 mg/kg dose, respectively. α‐Glucosidase and α‐amylase inhibitory activity of the extracts were also determined and both of the extracts inhibited α‐glucosidase enzyme strongly (64.29–75.22% at 2 mg/mL). Conversely, in vitro antioxidant activity and total flavonoid content of extracts were measured. The extracts were standardized by RP‐HPLC‐DAD on the basis of cynaroside and chlorogenic acid as markers. Practical applications: Bidens species have been used both as food and traditional medicine. In some countries, young leaves of Bidens species are added to salads, soups, and young shoot tips are used to make a tea. Our results revealed that Bidens species standardized by cynaroside and chlorogenic acid had a significant effect on regulation of blood glucose levels. It can be concluded that the tested Bidens species, that were found to be rich in flavonoid and phenolic compounds, might be beneficial for diabetic patients.